A Study on the Impact of Student Heterogeneity on the Implementation of Activity Based Oral English programme in primary classes - Rohan, R.M.D. (My University, 2004)
This is a study conducted on the impact of student heterogeneity in implementation of tivity Based Oral English by R. M. D. Rohan as partial fulfillment of the requirement for : degree of Master of Education. Teaching English to Speakers of Other languages. • The Kannangara report in 1943 which suggested to make vernacular languages the sdium of instruction, introduced a new subject to Sri lankan education system i.e. English as lecond language. Since the introduction, it started to be one of the subjects that attracted the lention of education researchers. Still, there is a problem about the age level at which Iglish should be introduced as a second language. Throughout the history of Sri lankan ucation after the independence. English has been tried to be introduced at different levels, le most recent attempt is introducing communicative English in ABOE as a part of ivironment Related Activities in grade 1. It is an accepted fact that from grade 1, students begin to show their individual Kerences and begin to build up as independent personalities acquiring their culture. These dividual differences are referred to as student heterogeneity and it is concerned in the search with ABOE. The research pays its attention on how the teachers can make use of iOE to minimize the student heterogeneity and its effects on learning teaching process.